Multiagent System to search and contracting Tourism services - Santanna Filho, João Ferreira de; Costa, Scheila Nair; Costa, Camila Pontes B. da; Szymanski, Charbel; Hornburg, João Eduardo (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper presents a multi-agent system (MAS) to integrate the service offerings of numerous companies of the tourism segment. This idea was motivated by world sporting events that will happen in the coming years in Brazil (FIFA World Cup and Olympics). The paper demonstrates that MAS’s can be a platform for integrating distributed systems resulting in more flexible systems with embedded intelligence.